LA INSTIGACIÓN O PERSUASIÓN AL SUICIDIO, MEDIANTE MALTRATO FÍSICO, PSICOLÓGICO O INFLUENCIA DE CREENCIAS RELIGIOSAS; Y, SU TIPIFICACIÓN Y PENALIZACIÓN EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL - Roa Solórzano, Jennifer Guadalupe (2019)
The present thesis seeks to provide, through scientific research, a solution to the problem posed, in relation to the increase in suicides worldwide, specifically in which the victims have been influenced to develop autolytic ideas, concluding in taking their own lives. When carrying out this study, it was possible to demonstrate a legal vacuum that verified that the right to life was not protected or protected in its totality by the State, given that the cases of instigation or persuasion to suicide, through psychological, physical abuse or influence of religious beliefs, are not sanctioned by our current legal regulations. This investigation consists of conceptual referents and doctrinal elements, which have allowed the understanding of the legal problematic and that, as a result of this investigative process, you have allowed to formulate as a proposal, the fact that a person who persuades or instigates another to end their lives, through physical, psychological or religious influences, should be punished with imprisonment of three to five years.